Carryover of herbicides used in cotton stalk control on soybean cultivated in succession - C. Francischini,Alessandra (2020)
Abstract Background: Information on the carryover of herbicides applied to the destruction of cotton stalks, as well as the withdrawal period necessary to prevent the development and productivity of the crop in succession from being affected are limited in the literature. Objective: The objective was to identify the carryover effect promoted by herbicides used in the management of the destruction of cotton stalks and to estimate the host free period for sowing soybean in succession. Methods: Two individual experiments were conducted simultaneously, one for single application and the other for sequential application of herbicide treatments. The experiments were installed in a factorial scheme (15x5), in a randomized block design with four replications. The first factor evaluated was herbicide treatments and the second factor was five soybean sowing times after application (0, 30, 60, 90 and 120 days). The herbicides used in the treatments were 2,4-D, glyphosate, saflufenacil, [imazapic + imazapyr], dicamba, fluroxypyr and sulfentrazone. Results: As this work was conducted, the results provide a carryover indicator. It is concluded that the single application and the sequential application of the glyphosate + dicamba + saflufenacil treatment has great carryover potential for soybean crops, with the host free period for sowing the crop exceeding 120 days after application. Conclusions: The treatments 2,4-D, 2,4-D + glyphosate, glyphosate + saflufenacil + fluroxypyr had the lowest host free period intervals, even when in sequential application. The treatment with application of 2,4-D alone showed the lowest carryover potential for soybean.